The theory of an ‘optimum currency area’ - Kundera, Jarosław (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
The main goal of this paper is to analyse and distinguish the main components of the theory of an ‘Optimum Currency Area’. The theory of an optimum currency area indicates some essential elements as preconditions for the successful introduction of a common currency: high mobility of labour, openness of the economy defined as a high proportion of tradable to non-tradable goods, and high diversification of domestic production before joining the union. The article’s analysis helps to better understanding the reasons of the current crisis in the euro zone. The main problem with a common currency area is the adjustment to imbalances, which cannot take place through exchange rates in conditions of a common currency. The missing elements of the theory are the role of the mobility of capital to correct interregional balance of payments disequilibria and lack of a common budget with sufficient own resources during the occurrence of debt crises in member countries. The theory of an optimum currency area has noticed the importance of coordination between fiscal and monetary policy and the necessity of redistribution of resources among partners. However, it does not say much about the methods applied, how to deal with debt crises and what the cost of a potential breaking up of monetary union would be.
Keywords: Optimum Currency Area; currency; current crisis; euro zone